Branchiostegus biendong, a New Tilefish from Vietnam (Perciformes: Branchiostegidae) - Hiramatsu, Wataru; Vinh, Chu Tien; Endo, Hiromitsu (Zootaxa, 2019)
A new tilefish, Branchiostegus biendong, is described on the basis of three specimens (181–209 mm in standard length [SL]) collected from a local fish market of Quy Nhon on the South China Sea coast of central Vietnam. It can be distinguished from 17 congeners in having the following combination of characters: six diagonal scale rows exposed on cheek; cheek scales moderately large (diameter 2.2–2.5% SL); predorsal ridge black; cheek almost silver with an oval-shaped, yellow blotch along ventral margin of eye; dorsal fin translucent yellowish with narrow black margin overlapping stronger yellowish coloration dorsally; upper lobe of caudal fin with 5–6 yellow stripes and tip with black blotch; and lower lobe of caudal fin navy blue. A key to five species of Branchiostegus from Vietnamese waters is provided.